Genotyping and phenotyping of platelet function disorders. (30th June 2013) - Watson, S. P.; Lowe, G. C.; Lordkipanidzé, M.; Morgan, N. V.
Summary: The majority of patients with platelet function disorders (PFDs) have normal platelet counts and mild day‐to‐day bleeding symptoms, but are at risk of major hemorrhage at times of trauma, surgery, or childbirth. This group is challenging to investigate, because the assays are often time‐intensive and labour‐intensive, and interpretation is difficult, especially in patients with mild disorders. In addition, interuser variability in performance of the assays, including the currently accepted gold standard, light transmission aggregometry, makes the results difficult to compare between laboratories. Furthermore, a similar pattern of mucocutaneous bleeding is seen in disorders in other components of the hemostatic pathway, including type 1 von Willebrand disease (VWD). We have undertaken an extensive investigation of patients with clinically diagnosed excessive bleeding, using a genotyping and platelet phenotyping approach based on lumi‐aggregometry, and other specialist tests of platelet function, in combination with Sanger and next‐generation sequencing (NGS). We found a functional defect in ~ 60% of patients, the majority being associated with feedback pathways of platelet activation. Function‐disrupting mutations were identified in known and novel genes, and coinheritance with other genetic disorders of hemostasis, including type 1 VWD, was shown. A significant number of mutations are heterozygous and unlikely to cause extensive bleeding in isolation, consistent with incomplete penetrance of inheritance of bleeding disorders and a multifactorial etiology for excessive bleeding in many patients. Mucocutaneous bleeding is a complex trait, and this has important implications for NGS in the assessment of a PFD.